Efektifitas Media Kokami terhadap Penguasaan Kosakata Bahasa Arab Kelas VIII SMPIT An Nur Gemolong - Riza Nur Laila; Melinda Cahyani; Habibah Nurul Azizah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Learning media is a tool used to convey messages so that it can stimulate students' thoughts, feelings, attention, and willingness in the learning process. This study aims to determine the effectiveness of using KoKaMi media, a three-dimensional media combined with language games, in improving Arabic vocabulary mastery of eighth-grade female students of SMPIT An Nur Sragen. This study uses a quantitative approach with an experimental method and a pre-experimental design of one group pretest–posttest type. The study population consisted of 22 female students and all were sampled through a total sampling technique. Data collection was carried out through tests, interviews, observations, and documentation, while data analysis used descriptive statistics, prerequisite tests, and hypothesis testing with the help of SPSS. The results of the analysis showed that the data were not normally distributed so the Wilcoxon Signed Rank Test was used. The test results showed a significance value of 0.000 smaller than 0.05, which means H0 is rejected and Ha is accepted. These findings prove that KoKaMi media is effective in improving Arabic vocabulary mastery. Therefore, KoKaMi media can be used as an alternative innovative learning media that helps students understand vocabulary more actively, enjoyably, and meaningfully. The implications of this research indicate that the use of game-based media can increase learning motivation, class participation, and learning interactions, so teachers are advised to utilize similar creative media as an effective and student-centered language learning strategy in learning practices at school consistently and sustainably.